Dampak Pembelajaran Berdiferensiasi Terhadap Hasil Belajar Matematika di Sekolah Dasar - Bayu Kurniawan; Anam Sutopo; Choiriyah Widyasari (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Mathematics plays an important role in shaping the cognitive abilities and critical thinking skills of elementary school students. However, the low learning outcomes in mathematics at the elementary school level are one of the main problems faced in the current educational world. Difficulty in understanding basic mathematical concepts is commonly experienced by students, which negatively impacts their overall academic achievement. This study aims to analyze the influence of differentiated learning on elementary school students' mathematics learning outcomes. This research uses a systematic literature review approach. The data used consists of articles published from 2022 to 2024, totaling 200 articles. From the 200 articles, 12 articles were selected based on inclusion and exclusion criteria. The results of this study can be concluded that: (1) differentiated learning by considering learning styles can improve students' mathematics learning outcomes; (2) differentiated learning can be combined with other learning models; (3) differentiated learning can be effective in improving students' mathematics learning outcomes in elementary schools; and (4) differentiated learning for mathematics education in elementary schools can make students interested in participating in the learning process.